Two little monkeys - Fox, Mem, 1946-; Barton, Jill (New York : Beach Lane Books, 2012)
A rhyming tale about two little monkeys who are hiding from a leopard.
Booklist
Kirkus Starred
Publisher's Weekly
Booklist, March 2012
Kirkus Starred, March 2012
Publisher's Weekly, March 2012
Keywords: Leopard -- Juvenile fiction; Monkeys -- Juvenile fiction; Leopard -- Fiction; Monkeys -- Fiction; Stories in rhyme; Leopards -- Fiction; Monkeys -- Fiction; Stories in rhyme; Picture books for children